Tonotopic organization of the hyperpolarization-activated current (Ih) in the mammalian medial superior olive - Baumann, Veronika; Lehnert, Simon; Leibold, Christian; Koch, Ursula (Frontiers in Neural Circuits, 2013)
Abstract Neuronal membrane properties can largely vary even within distinct morphological cell classes. The mechanisms and functional consequences of this diversity, however, are little explored. In the medial superior olive (MSO), a brainstem nucleus that performs binaural coincidence detection, membrane properties at rest are largely governed by the hyperpolarization-activated inward current (Ih) which enables the temporally precise integration of excitatory and inhibitory inputs. Here, we report that Ih density varies along the putative tonotopic axis of the MSO with Ih being largest in ventral, high-frequency processing neurons. Also Ih half-maximal activation voltage and time constant are differentially distributed such that Ih of the putative high-frequency processing neurons activate faster and at more depolarized levels. Intracellular application of saturating concentrations of cyclic AMP removed the regional difference in hyperpolarization-activated cyclic nucleotide gated (HCN) channel activation, but not Ih density. Experimental data in conjunction with a computational model suggest that increased Ih levels are helpful in counteracting temporal summation of phase-locked inhibitory inputs which is particularly prominent in high-frequency neurons.